Myelin characteristics of the corpus callosum in capuchin monkeys (Sapajus [Cebus] apella) across the lifespan - Chase M. Watson; Chet C. Sherwood; Kimberley A. Phillips (Scientific Reports, 2022)
Abstract The midsagittal area of the corpus callosum (CC) is frequently studied in relation to brain development, connectivity, and function. Here we quantify myelin characteristics from electron microscopy to understand more fully differential patterns of white matter development occurring within the CC. We subdivided midsagittal regions of the CC into: I—rostrum and genu, II—rostral body, III—anterior midbody, IV—posterior midbody, and V—isthmus and splenium. The sample represented capuchin monkeys ranging in age from 2 weeks to 35 years (Sapajus [Cebus] apella, n = 8). Measurements of myelin thickness, myelin fraction, and g-ratio were obtained in a systematic random fashion. We hypothesized there would be a period of rapid myelin growth within the CC in early development. Using a locally weighted regression analysis (LOESS), we found regional differences in myelin characteristics, with posterior regions showing more rapid increases in myelin thickness and sharper decreases in g-ratio in early development. The most anterior region showed the most sustained growth in myelin thickness. For all regions over the lifespan, myelin fraction increased, plateaued, and decreased. These results suggest differential patterns of nonlinear myelin growth occur early in development and well into adulthood in the CC of capuchin monkeys.